Mencari Spiritualitas Misioner Komunitas Basis Gerejawi - Raymundus I Made Sudhiarsa (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2008)
The article describes that Basic Christian Community is primarily the real way of being Church. It is the actual community of Christ that inspired and oriented by the teaching and life example of Jesus Christ (e.g. Matt 5-7; Lc 6:20-21.24-25). In this sense, it is an alternative and prophetic community, a kind of 'counter culture' that lives out radical values which are contrary to most values of other human communities. Exactly in this way that Christian community will be able to realize its mission to be a lumen gentium and gaudium et spes for the world. In so doing Christian communities are expected to initiate and promote transformation of the local society and the world in general. The writer also highlights the need to consider Basic Christian Community as a 'school of dialogue' for the Christians. Exactly in this very place they are called to learn from one another the way to internalize Christian values, a 'new' way of living and believing in a humane community. He believes that everybody who is serious about his/her Christian faith will be committed in the twofold calling, namely communio et missio. Meaning, being Church is being for others, for the Church exists is not only for herself (communio), but primarily for the salvation of the world (missio). Therefore, the writer tries to propose the so-called mission spirituality for the life of Basic Christian Community, which is the spirituality of discipleship.